Pengembangan Alat Ukur Metode Observasi Rating Scale : Perilaku Emosi Marah Dan Temper Tantrum Pada Anak Usia Dini - Denok Wigati; Wardatul Mufidah (IDEA: Jurnal Psikologi, 2022)
The development of a rating scale for angry behaviour and temper tantrum includes the preparation of a 40-item rating scale. Trials involving 50 infants with empirical validity and reliability tests. Validity test using the SPSS (statistical package for the social sciences) application. Results from the empirical validity test showed that there were 31 valid elements among the 40 tested and analyzed elements. The valid index varies between 0.259 and 0.643. The Cronbach's Alpha index or rtt = 0.832 (rtt > 0.07) means that the rating scale for angry behavior & temper tantrums is reliable.